Of Short Interspersed Nuclear Elements, Long Interspersed Nuclear Elements and Leeches: Identification and Molecular Characterization of Transposable Elements in Leech Genomes - Christian Müller (DNA)
Backround/Objectives: Mobile genetic elements (MGEs), in general, and transposable elements (TEs), in particular, constitute a major part of almost every eukaryotic genome, and several types of such elements have been classified based on size, genetic structure and transposition intermediate. Methods: The fast-growing availability of whole genome sequences of species across the living world provides almost unlimited possibilities for in-depth molecular analyses of all kinds, including the search for TEs. The aim of the present study was to perform the first molecular description and characterization of selected MGEs in leeches, namely, short interspersed nuclear element (SINE), long interspersed nuclear element (LINE) and long terminal repeat (LTR) retrotransposons. Results: Several representatives of all three groups of TEs could be identified, and some of the newly described elements display unique structural features compared to the archetype elements of the respective groups. Conclusions: Non-model organisms like leeches are an excellent source for new information on long-term studied objects like TEs and may provide new insights into the diversity and the putative biological impact of these MGEs.